A Strategy Using Robotics to Assist in the Process of Teaching and Learning Kinematics - Junior, Almir; Neto, João; Guedes, Elloá (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
We hope that with Physics classes students can improve their comprehension of the world trough concepts observation and phenomenon experimentation in practice. Considering this perspective, this work introduces the description of the design and application of a strategy using Robotics to support the teaching learning process of uniform rectilinear motion and of uniformly varied rectilinear motion. The results emphasize that this strategy can help students to comprehend, in a contextualized way, the theories and scientific phenomenons existing in Physics.